PENERAPAN PSYCHOLOGICAL METHOD UNTUK MENINGKATKAN MENTAL DAN ASOSIASI PIKIRAN DALAM PEMBELAJARAN BAHASA ARAB - Nala Sarif Fauziatun; Chairani Astina (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2018)
the application of psychological method is expected that students can accept and be able to master the learning of Arabic, because the application of psychological method is a method used in each learning activity, especially language learning, by looking at the conditions of mental development and association of students' minds.This study aims to: 1) To find out some application of psychological method in learning Arabic class VII MTS Ma'arif Selomerto Wonosobo; 2) To know the improvement of students' mental from the learning of Arabic class VII MTS Ma'arif Selomerto Wonosobo; 3) To find out an increase in student's mind association from the learning of Arabic class VII MTS Ma'arif Selomerto Wonosobo.Research with experimental method using design of One Group Pretest-Posttest Design. Subjects in this study are students of class VII C MTs Ma'arif Selomerto which amounted to 27 students who made experimental class. Before the experimental class study was given a questionnaire and a pretest question. Students of the experimental class were given a study using psychological method (psychological method). The experimental class is subject to a final test in the form of a written test. Then the results are processed, analyzed, using the T-test to determine the mental improvement and mind associations of students studied.The results showed that: 1) Arabic learning for mental and mind associations of students in MTs Ma'arif Selomerto using psychological method (psychological method) with the steps on the learning; 2) Improvement of students' mental experiment class by 10,88; 3) Improved mind association of experimental class students 73,85; 4) There is an increase in mind association of students in the experimental class with tcount = 73,85; <ttable = 2,064. So that Ha accepted and Ho rejected.